Dynamic and self-biodegradable polysaccharide hydrogel stores embryonic stem cell construct under ambient condition - Yang, Kuan; Wei, Wei; Gao, Li Ting; Zhao, Xin Yi; Liu, Zhenqi; Li, Jianhui; Li, Haopeng; Miyatake, Hideyuki; Ito, Yoshihiro; Chen, Yong Mei (Frontiers in Bioengineering and Biotechnology, 2023)
The proper microenvironment is critical for the storage and transportation of embryonic stem cells (ESCs). To mimic a dynamic 3D microenvironment as it exists in vivo and consider “off-the-shelf” availability reaching the destination, we proposed an alternative approach that allows for facile storage and transportation of stem cells in the form of ESCs-dynamic hydrogel construct (CDHC) under ambient conditions. To form CDHC, mouse embryonic stem cells (mESCs) were in-situ encapsulated within a polysaccharide based dynamic and self-biodegradable hydrogel. After storing CDHC in a sterile and hermetic environment for 3 days and then transferring to a sealed vessel with fresh medium for another 3 days, the large and compact colonies retained 90% survival rate and pluripotency. Furthermore, after transporting and arriving at the destination, the encapsulated stem cell could be automatically released from the self-biodegradable hydrogel. After continuous cultivation 15 generations of retrieved cells, automatically released from the CDHC, the mESCs underwent 3D encapsulation, storage, transportation, release and continuous long-term subculture, resumed colony forming capacity and pluripotency which were revealed by stem cell markers both in protein and mRNA levels. We believe that the dynamic and self-biodegradable hydrogel provides a simple, cost-effective and valuable tool for storing and transporting “ready-to-use” CDHC under ambient conditions, facilitating "off-the-shelf" availability and widespread applications.